1989
DOI: 10.1016/1010-7940(89)90115-2
|View full text |Cite
|
Sign up to set email alerts
|

Brain histology, blood-brain barrier and brain water after normothermic and hypothermic cardiopulmonary bypass in pigs

Abstract: The effect of hypothermia during cardiopulmonary bypass (CPB) on cerebral histopathology, blood-brain barrier permeability to serum proteins and water content was evaluated. Pigs were subjected to non-pulsatile CPB for 2 h at either normothermia or hypothermia, and a group of anaesthetised pigs served as normothermic controls. The histopathology was assessed on paraffin embedded sections. The permeability of the cerebral vessels was studied by immunocytochemical demonstration of extravasated serum proteins. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Our data indicate that phenylephrine does not potentiate cerebral vascular resistance nor alter cerebral perfusion per se. Further, our study supports the findings PHENYLEPHRINE DURING CARDIOPULMONARY BYPASS of other investigators where the integrity of the bloodbrain barrier was directly examined using radioactive tracers (14) or immunochemistry (15). Under other circumstances when the integrity of the blood-brain barrier is altered, such as occurs with cold injury (2), mercuric dichloride (2), hypertonic urea (1 ), increased intravascular pressure (16), cerebral infarction (17), or closed head injury (18)) brain edema rapidly ensues.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our data indicate that phenylephrine does not potentiate cerebral vascular resistance nor alter cerebral perfusion per se. Further, our study supports the findings PHENYLEPHRINE DURING CARDIOPULMONARY BYPASS of other investigators where the integrity of the bloodbrain barrier was directly examined using radioactive tracers (14) or immunochemistry (15). Under other circumstances when the integrity of the blood-brain barrier is altered, such as occurs with cold injury (2), mercuric dichloride (2), hypertonic urea (1 ), increased intravascular pressure (16), cerebral infarction (17), or closed head injury (18)) brain edema rapidly ensues.…”
Section: Discussionsupporting
confidence: 89%
“…Under other circumstances when the integrity of the blood-brain barrier is altered, such as occurs with cold injury (2), mercuric dichloride (2), hypertonic urea (1 ), increased intravascular pressure (16), cerebral infarction (17), or closed head injury (18)) brain edema rapidly ensues. Because measurements of brain water content (12,15,19,20) as well as intracranial compliance (12) show no alteration by hypothermic CPB, edemagenesis in the brain secondary to bypass is apparently limited or at least undetectable using these techniques. Thus, the tight interendothelial junctions of the cerebral vasculature do not appear to be disrupted by CPB when bubble or membrane oxygenators are used, or by gaseous microemboli during the course of CPB.…”
Section: Discussionmentioning
confidence: 99%
“…[3, 7, 8] Our study used a contrast agent (gadobutrol) that is not only detectable in processed brain tissue, but permits in vivo administration allowing survival analysis. This approach thus renders animal-based studies with serial neurological exams possible, and furthermore, since gadobutrol is an intravenous contrast agent approved for patient use, is directly applicable to clinical studies.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work characterising BBB permeability after CPB/DHCA has mostly relied on detection of extravasation of large macromolecular proteins, such as albumin. Using this approach some studies have found no evidence of BBB disruption,[7] while others have detected it after only 30 minutes of CPB. [8]…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms underlying this susceptibility are not completely understood. Moreover, some studies have not demonstrated blood CSF barrier dysfunction and leakage of plasma proteins from CPB 8, 9…”
Section: Introductionmentioning
confidence: 99%